Perbandingan Remifentanil Kontinu 0.15 Mcg/Kgbb dengan Fentanyl 3 Mcg/Kgbb pada Intubasi Endotrakeal Diukur Menggunakan Pupillometer (AlgiScan®) - Fauzan Bachtiar Amin; Alamsyah A.A Husain; Andi Muhammad Takdir Musba; Muh Ramli Ahmad (Nusantara Medical Science Journal, 2020)
Introduction: All opioids have varying levels of sedative effects with increasing dosages, although with different strengths. Therefore, the opioid component as a sedative regiment is usually maintained at minimum dose for adequate analgesic with regard to patient comfort. Along with the progress of knowledge, parameters have been found to measure the level of analgesic and sedative. Methods: The principle of measurement is done by using the diameter of pupil and then analyzed through AlgiScan and compared to certain standards. The using of pupilometers AlgiScan in assessing the level of sedative analgesic will reduce the level of subjectivity and errors in measurement. Results: The use of Remifentanil has a faster effect of sedative as proven by lower “AlgiScan” score in the pre-intubation phase. In addition, the use of Remifentanil also provides a hemodynamic view of lower arterial pressure, both pre and post intubation condition. Conclussion: Both Remifentanil and fentanyl are able to provide analgesic with sedative and stable hemodynamics. Remifentanil is proven to be superior with better and faster effect and also faster substance elimination with lower doses.